Возможность использования культуры Gluconobacter oxydans 2T в области ремедиации почв от гербицида 2,4,5-Т - Жарикова, Н.В.; Коробов, В.В.; Анисимова, Л.Г.; Ясаков, Т.Р.; Журенко, Е.Ю.; Маркушева, Т.В. (Фактори експериментальної еволюції організмів, 2010)
Штамм Gluconobacter oxydans 2Т был выделен из смешанных почвенных популяций бактерий. Культура способна утилизировать 2,4,5-Т как единственный источник углерода и энергии. В периодической культуре G. oxydans утилизировал 81% 2,4,5-Т за 9 дней. Среди метаболитов были выявлены 2,4-дихлорфеноксиуксусная, 4-хлорфеноксиуксусная и 3-метил-2,6-диоксо-4-гексеновые кислоты. Степень очистки почвы, достигаемая при использовании штамма G. oxydans 2T, составила 66,5% к 48-м суткам. The strain Gluconobacter oxydans 2T has been isolated from a soil mixed bacterial populations. G. oxydans 2T is capable of utilizing 2,4,5-Т as the sole source of carbon and energy. 2,4,5-Т quantity was reduced in a culture medium approximately on 81% by G. oxydans 2T batch culture within 9 days. The strain produced processes of 2,4,5-Т dehalogenation to phenoxyactic acid, which then was transformed to 3-methyl-2,6-dioxo4-hexenoic acid. The culture G. oxydans 2T utilizes 2,4,5-Т in soil. The 2,4,5-Т concentration was reduced approximately on 67% within 48 day.